Who dares, wins: Heroism versus altruism in women's mate choice - Kelly, S; Dunbar, R (2001)
Heroism is apparently nonadaptive in Darwinian terms, so why does it exist at all? Risk-taking and heroic behavior are predominantly male tendencies, and literature and legend reflect this. This study explores the possibility that heroism persists in many human cultures owing to a female preference for risk-prone rather than risk-averse males as sexual partners, and it suggests that such a preference may be exploited as a male mating strategy. It also attempts to quantify the relative influences of altruism and bravery in the evolution of heroism. Our study found that females do prefer risk-prone brave males to risk-averse non-brave males, and that men are aware of this preference. Bravery in a male was shown to be the stronger factor influencing female choice of short-term partners, long-term partners, and male friends, with altruism playing a lesser part in their choice. Altruism was deemed important in long-term relationships and friendships, but for short-term liaisons, non-altruists were preferred to altruists. Heroism may therefore have evolved owing to a female preference for brave, risk-prone males because risk-taking acts as an honest cue for "good genes." Altruism was judged to be a less influential factor in the evolution of heroism than bravery and a demonstrated willingness to take risks.